INTERFERENSI LEKSIKAL DALAM SURAT KABAR BANYUMASEKSPRES EDISI NOVEMBER 2022 DAN RELEVANSINYA TERHADAP PEMBELAJARAN TEKS BERITA - Meysyah Vigiyanti; Helmi Seftiani; Agnes Apryliana (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The purpose of this study was to analyze the form of lexical interference in the November 2022 edition of the Banyumas Ekspres newspaper with newt text learning materials. This research  is part of  a qualitative descriptive research. Obtaining data in this study used the listening method, then recorded information abaout language interference contained in the November 2022 edition of the Banyumas Ekspres newspaper. The result of of the data recording were then transferred to a data card containing data and information codes. The method used in this study is the equivalent method. Based on data analysis carried out by researchers, the data found in the November 2022 edition of the Banyumas Ekspres newspaper contained three forms of lexical interference which included basic word forms, affixed words, and repeated words. The following inb the result of research on the forms of  lexical interference in the November 2022 edition of the Banyumas Ekspres newspaper, so it can be concluded as follows: The most common form pf Javanese lexical interference in indonesian is the basic word form, totaling 26 data. Another form of lexical interference that appears is the form of affixed words with 18 data, and 6 data for repeated words.